Mechanical activation of magnesium silicates for mineral carbonation, a review - Li, Jiajie; Hitch, Michael (Minerals engineering, 2018)
•Olivine and serpentine behave differently with respect to mechanical activation.•Mechanical pre-treatment is effective to activate olivine containing materials.•Combining chemical and mechanical activation is favorable to activate serpentine.•An integrated mineral carbonation process may put mechanical activation into practice. Mechanical activation is one of the most efficient pretreatment methods used to accelerate the reaction rate in the mineral carbonation technology. This paper reviews the current research related to this technique with a specific focus on three types of magnesium silicates - olivine and serpentine, and partially serpentinized olivine. First, the effects of mechanical activation on magnesium silicates are listed and compared with regard to a variety of milling conditions, including diverse energy inputs, grinding aids and mill types. Then, the existing literature determines the extents of mechanical activation, reviewed with respect to downstream carbonation processes, including direct gas/solid carbonation, direct aqueous carbonation, indirect aqueous carbonation, and indirect solid/solid mechanochemical carbonation. Finally, suggestions are made for further study on applying mechanical activation in an integrated mineral carbonation process, in order to lower the energy consumption of commercial systems.